Berakhirnya Kepemimpinan Kharismatik Islam Radikal di Indonesia - Chaidar, Al; Subhani, Subhani; Apridar, Apridar (PASAI, 2014)
A number of publications made by the Jamaah islamiyyah terrorist group which derived from the Darul Islam will be analyzed to see how far the terrorist mind-set of Aceh in performing movements, why they react to the idea of democracy, and how they formulate Islamic caliphate, Islamic state, the establishment of Islamic law and how it relates to other Islamic religious groups in Indonesia. Among the Islamic groups those support terrorist movements in Indonesia so far and also by way of what support was given, it is still a mystery that needs to be answered through this research. It is also interesting to find out the orientation of the clergy thought that was referred by the terrorists in Aceh. During this time, the clerics of Darul Islam have been partially supported armed political movements against the government of the Republic of Indonesia but why and how they refused to participate in terrorism. Are there any scholars of the modern pesantren, or traditional Islamic boarding school, who participated in sort of moral support to terrorist groups in Indonesia? And many other questions that need to get an answer through this study.